ANALISIS PENGULANGAN (REPEAT) RADIOGRAFI PADA MODALITAS DIGITAL RADIOGRAFI (DR) DI INSTALASI RADIOLOGI RSU PKU MUHAMMADIYAH BANTUL - M. Efendi; Ayu Mahanani; Asih Puji Utami (Bajang Institute, 2026)
Background: Digital Radiography (DR) is a digital imaging system that replaces conventional film with digital detectors to produce faster and more efficient diagnostic images. Although this technology has the ability to correct contrast and density errors, repeat examinations still occur due to patient positioning errors, artifacts, and other technical factors. Based on preliminary data from the Radiology Installation of PKU Muhammadiyah Bantul Hospital, image repeats have never been thoroughly analyzed, even though repeats affect radiation dose increases and radiographers' work efficiency. Objective: This study aims to determine the percentage level of repeat radiography and identify the factors causing repeat examinations using the Digital Radiography (DR) modality at the Radiology Installation of PKU Muhammadiyah Bantul Hospital. Method: The study used a qualitative approach with a case study design. Data were collected through direct observation, interviews with three radiographers, and documentation of examination data during April–June 2025. Interview data analysis included interview transcripts, data reduction, coding, categories, and themes, followed by conclusions. The repeat results were analyzed descriptively by calculating the percentage of repeats and grouping the causes of repeats based on technical and human error categories. The results were used to assess the implementation of Quality Assurance (QA) and Quality Control (QC) programs in the radiology installation. Results: Of the total 4,835 radiographic examinations, 35 cases of repeat cases (0.73%) were found, which is below the maximum limit of ≤2% as stipulated in KMK No. 129/Menkes/SK/II/2008. The main factors causing repeat cases were cut objects (0.44%) and artifacts (0.38%), followed by minor cases due to cassettes not being ready (0.12%). Although most radiographers understand the theory and working principles of DR, there is still a mismatch between theory and practice in patient positioning and pre-exposure examination. Conclusion: The results of the study showed that the repeat rate of radiography at PKU Muhammadiyah Bantul General Hospital was classified as very good (0.73%), indicating the implementation of effective and efficient radiology quality management. These results confirm that radiographers have implemented the principles of QA, QC, and ALARA (As Low As Reasonably Achievable) well, thus reducing repeats below national standards. The main error factors come from human error aspects such as patient positioning and metal artifacts, not equipment damage. Regular evaluation, technical training, and increased accuracy in patient positioning are needed to maintain image quality and patient safety continuously.